Training Model for Injury Prevention in Archery: A Literature Study - Asy Syahidah, Annisa; Fatoni, Muhad; Warthadi, Anugrah Nur (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Semarang, 2024)
Background: Sports injuries are a problem that occurs in athletes both during, competing, and after training. The injury gets worse If incorrectly treated. This research explores a literature review study on injury management training models for archery athletes. Method: This research is limited to injuries that often occur in archery sports, analysis of the physical needs of archery sports, and archery injury prevention training models taken in 20 journals, both international and national. Result: The results showed that in archery, injuries to the upper body are the most common (shoulder, finger, and hand injuries) and are also frequently reported. The factors that cause most injuries are internal factors (technical errors or movements when playing) and external factors (the environment or bad weather while playing). Injury management models include the sequence of prevention of sports injuries; dynamic and recursive models of sports injury etiology; and comprehensive models of injury causes. The training models for Injury Prevention in Archery were Body Mass Density (BMD); Range of Motion (ROM); Translation Research Model of Injury Prevention Practice (TRIPP), the Haddon Matrix model, the decision-based RTP model; and the Team-sport Injury Prevention (TIP) model. Conclusion: The literature on injury prevention in archery reveals that, although the sport is generally considered low-impact, it presents unique physical demands that can lead to both acute and chronic injuries, particularly in the shoulder, elbow, and back.